Insulin Gene/IDDM2 Locus in Japanese Type 1 Diabetes: Contribution of Class I Alleles and Influence of Class I Subdivision in Susceptibility to Type 1 Diabetes - Awata, Takuya; Kawasaki, Eiji; Ikegami, Hiroshi; Kobayashi, Tetsuro; Maruyama, Taro; Nakanishi, Koji; Shimada, Akira; Iizuka, Hiroyuki; Kurihara, Susumu; Osaki, Masataka; Uga, Miho; Kawabata, Yumiko; et al. (The journal of clinical endocrinology and metabolism, 2007)
Context: It is suggested that insulin autoimmunity plays an important role in the development of type 1 diabetes in humans. However, the association between insulin gene (INS) region (IDDM2) and type 1 diabetes has been uncertain in Asians. Objective: A multicenter collaboration study was conducted to clarify the role of the IDDM2 region in Japan. Subjects and Methods: In total, 661 patients with type 1 diabetes and 706 control subjects were enrolled. The INS variable number of tandem repeat (VNTR) class I/class III status was estimated by genotyping the −23 HphI single nucleotide polymorphism. From surrounding polymorphisms across the insulin gene, we also inferred haplotypes bearing INS VNTR lineages. Results: The frequency of the class I allele was 99.3% in patients and 96.7% in controls (P < 10−5), and the class I/III or III/III genotype was found in 1.4% of patients and in 6.4% of controls [odds ratio (OR) 0.20, P < 10−5]. The class I subdivision revealed IC to increase significantly in patients with type 1 diabetes (P = 0.002), whereas ID did not; the distribution of IC and ID was significantly different between patients and controls (P = 0.014). Conclusion: The present study certainly shows that the IDDM2 region is also a susceptibility locus in the Japanese population. Furthermore, it was revealed that IC may be more susceptible to type 1 diabetes than ID, which could be evidence that the INS VNTR itself confers susceptibility to type 1 diabetes.